Sleep quality among pre-clinical medical students in Universiti Putra Malaysia and Universiti Malaya, Malaysia - Masalamany, Krishnaraja; Sie, Tien Ngu; Abd Manan, Nizar; Adam, Siti Khadijah (KKMED Publication, 2017)
Introduction: Poor sleep quality among university students seems to be an important issue to be concerned. It can give great impact on students especially on their academic performance. However, studies regarding sleep quality on medical students in Malaysia are limited. Objective: The objective of this study was to determine the sleep quality of pre-clinical medical students in Universiti Putra Malaysia (UPM) and Universiti Malaya (UM). Methods: This was a cross-sectional study. Self-administered questionnaire was used to collect data from the pre-clinical medical students of UPM and UM. Sleep quality of the students was measured by Pittsburgh Sleep Quality Index (PSQI) questionnaire. All the data were analysed by using SPSS version 21. Results: The study revealed that 63.9% of the respondents had poor sleep quality (PSQI score: more than 5). The prevalence of poor sleepers in UM (67%) was slightly higher than UPM (60.9%). However, the comparison of PSQI score showed no significant difference between UPM and UM respondents (p = 0.082). The average sleep duration per night among respondents was 5 hours 39 minutes (1.21 hrs). Only 6.1% of students practiced recommended sleep value per night (>7 hrs). Significant association was found between caffeine intake with sleep quality. Besides, our study showed no association between sleep quality with gender and year of study. Conclusion: Majority of the pre-clinical students in UPM and UM had poor sleep quality and short sleep duration. Only a small number of students practiced recommended sleep value per night.